Red light-triggered photoreduction on a nucleic acid template. Issue 69 (30th July 2020) - Dutta, Subrata; Rühle, Jennifer; Schikora, Margot; Deussner-Helfmann, Nina; Heilemann, Mike; Zatsepin, Timofei; Duchstein, Patrick; Zahn, Dirk; Knör, Günther; Mokhir, Andriy
Abstract : Conjugate Sn(iv )(pyropheophorbide a)dichloride–(peptide nucleic acid) catalyzes reduction of azobenzene derivatives in the presence of complementary nucleic acid (NA) upon irridiation with red light (660 nm) Abstract : Conjugate Sn(iv )(pyropheophorbide a)dichloride–(peptide nucleic acid) catalyzes reduction of azobenzene derivatives in the presence of complementary nucleic acid (NA) upon irridiation with red light (660 nm). This is the first red light-induced NA-templated photoreduction. It is highly sensitive to single mismatches in the NA-template and can detect down to 5 nM NAs.